2012
DOI: 10.1155/2012/582352
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of SLE: Functional Relevance for Monocytes/Macrophages in Disease

Abstract: Genetic studies in the last 5 years have greatly facilitated our understanding of how the dysregulation of diverse components of the innate immune system contributes to pathophysiology of SLE. A role for macrophages in the pathogenesis of SLE was first proposed as early as the 1980s following the discovery that SLE macrophages were defective in their ability to clear apoptotic cell debris, thus prolonging exposure of potential autoantigens to the adaptive immune response. More recently, there is an emerging ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 158 publications
1
33
0
1
Order By: Relevance
“…A percentage of SLE patients exhibits a loss in Trex1 function (8). In addition, we have shown that both TLR7 and TLR9 (19), which have been associated with the development of SLE, upregulate Trex1, and that, in its absence, responses to these TLR ligands result in an augmented inflammatory response.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A percentage of SLE patients exhibits a loss in Trex1 function (8). In addition, we have shown that both TLR7 and TLR9 (19), which have been associated with the development of SLE, upregulate Trex1, and that, in its absence, responses to these TLR ligands result in an augmented inflammatory response.…”
Section: Discussionmentioning
confidence: 79%
“…In SLE and other autoimmune diseases, a plethora of immune cells are dysfunctional, including T and B cells, which together result in high levels of circulating autoreactive Abs (18). Macrophages from SLE patients are more active, with increased cytokine production and an increase in the ability to present self-Ags to T cells, together with a decreased ability to perform apoptotic clearance (19).…”
mentioning
confidence: 99%
“…Since aberrant T cells polarization, altered HO-1 expression (3234) and/or monocyte activity (3537) have been reported in various inflammatory diseases, it raises the possibility that the CD16+monocyte HO-1-T cell polarization axis may also play a pivotal role in the etiology and prognosis of such inflammatory diseases. HO-1 activity and levels can be regulated by multiple factors, (9) and therefore understanding the mechanisms of HO-1 mediated T cell polarization may not only provide insight into the etiology of diseases and but also may offer potential therapy targets for such diseases.…”
Section: Discussionmentioning
confidence: 99%
“…studies have identified a number of genes that are linked to IFN production or signaling, such as IRF5, TYK2, IFIH1, and TLR7 (16,17). Type I IFNs have also recently been found to be central to inflammatory responses in the lung in response to viral or environmental challenges.…”
Section: Introductionmentioning
confidence: 99%